"You are the only other person in the world that knows that about me": Family physician stories of proximity to patients experiencing social inequity - Monica L. Molinaro; Katrina Shen; Chitrini Tandon; Gina Agarwal; Gabrielle Inglis; Meredith Vanstone (Elsevier, 2024)
Canadians' health outcomes are inextricably tied to social inequities. Family medicine is uniquely situated to provide care that addresses social factors through longitudinal knowledge of patients and the contexts of their lives. However, family physicians have come under increased practice demands shaped by neoliberal ideological structuring of health care, compounding difficulties in providing care for persons experiencing health needs related to social inequities. Nursing scholar Ruth Malone has argued that remaining proximal, or close to patients, is a form of resistance to these demands. Using a critical narrative methodology, this paper presents the stories of 20 family physicians working with persons experiencing health needs related to inequity in Ontario, Canada, that express and expand upon Malone's proximity. We highlight how participants invoke notions of proximity through their stories, describing the role of the family physician in: i) generating physical proximity based on the patients' needs for more time, space, and care; ii) developing narrative proximity through storytelling over time in these shared spaces, both between colleagues and patient communities; and iii) engaging in moral proximity, or recognizing the vulnerabilities of their patients, by going "above and beyond" in their care and advocacy roles inspired by the needs of their patients. The findings add theoretical depth to proximity, extending this conceptualization into a new clinical context. These stories also complement current health services and health policy research that advocates for collaborative primary care approaches, as elements of these approaches are conducive to establishing proximity with patients who need care the most.